The B Lymphocyte-Specific Coactivator BOB.1/OBF.1 Is Required at Multiple Stages of B-Cell Development - Hess, Jochen (American Society for Microbiology, 2001)
The transcriptional coactivator BOB.1/OBF.1 confers B-cell specificity on the transcription factors Oct1 and Oct2 at octamer site-containing promoters. A hallmark of the BOB.1/OBF.1 mutation in the mouse is the absence of germinal center development in secondary lymphoid organs, demonstrating the requirement for BOB.1/OBF.1 in antigen-dependent stages of B-cell differentiation. Here we analyzed earlier stages of B lymphopoiesis in BOB.1/OBF.1-deficient mice. Examination of B-cell development in the bone marrow revealed that the numbers of transitional immature (B220(+) IgM(hi)) B cells were reduced and that B-cell apoptosis was increased. When in competition with wild-type cells, BOB.1/OBF.1(−/−) bone marrow cells exhibited defects in repopulating the bone marrow B-cell compartment and were unable to establish a presence in the periphery of host mice. The defective bone marrow populations in BOB.1/OBF.1(−/−) mice were rescued by conditional expression of a BOB.1/OBF.1 transgene controlled by the tetracycline gene expression system. However, the restored populations did not restore the numbers of IgD(hi) B cells in the periphery, where the BOB.1/OBF.1 transgene was not expressed. These results show that BOB.1/OBF.1(−/−) B cells exhibit multistage defects in B-cell development, including impaired production of transitional B cells and defective maturation of recirculating B cells.